The Effect of Muscle Strength Training Using Resistance Bands on Student Disc Throwing Results - Maulana, Muhammad Andi; Setiawan, Moch Iman; Praja, Handayani Nila; Sundari, Sri (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The purpose of this study is to determine 1) The effect of learning results using resistance bands on the results of discus throwing throws, 2) The effect of learning outcomes using resistance bands on learning outcomes of discus throwing techniques, 3) Comparison of the results of discus throwing techniques and throws using resistance bands on the learning outcomes of students of SMK Negeri 1 Cirebon. Materials and methods. The research used was an experimental pretest-posttest group design. The population in this study was class X students of SMK Negeri 1 Cirebon, totalling 718 students. This study used purposive sampling technique, with the sample being class X students of SMK Negeri 1 Cirebon totalling 71 students. Data collection instruments include the results of pretest and posttest discus throwing techniques and throws. Results. The research shows that (1) There is an effect of learning outcomes using resistance bands on the results of discus throwing techniques, with a tcount value of 41.485> ttable value of 1.667 and a significance value of 0.000 <0.05. (2) There is an effect of learning outcomes using resistance bands on the results of discus throwing, with a tcount value of 25.722> ttable value 1.667 and a significance value of 0.000 <0.05. (3) There is an increase in learning outcomes of techniques and throws in throwing discs using resistance bands, with a percentage of technical results of 4.10% and throwing results of 5.77%. Conclusion. The results of data processing using the SPSS 26 assistance application, there is an effect of training using resistance bands on the results of techniques and throws of discus throwing students in class X SMK Negeri 1 Cirebon, this is evidenced by the results of techniques and throws there is an increase in pretest and posttest.